Discourse Markers in Early Semitic, and their Reanalyses in Subsequent Dialects - Blejer, Hatte Anne Rubenstein (1986)
Ph.D. Dissertation; -m and -s/-š; Supervising Professor: Winfred P.Lehmann. Order No. DA 8618423; DissAbstr 47/05 (Nov. 1986) 1712- A—1713-A.